Acute Kidney Disease in Hospitalized Pediatric Patients With Acute Kidney Injury in China - Deng, Ying-Hao; Yan, Ping; Zhang, Ning-Ya; Luo, Xiao-Qin; Wang, Xiu-Fen; Duan, Shao-Bin (Frontiers in Pediatrics, 2022)
Objective: The epidemiology and outcomes of acute kidney disease (AKD) after acute kidney injury (AKI) in hospitalized children are poorly described. The aim of this study is to investigate the prevalence, predictive factors and clinical outcomes of AKD in hospitalized children with AKI. Methods: Children (one month - 18 years) with AKI during hospitalization in the Second Xiangya Hospital from January 2015 to December 2020 were identified. AKD was defined based on the consensus report of the Acute Disease Quality Initiative 16 workgroup. The endpoints include adverse outcomes in 30 days and 90 days. Multivariable logistic regression analyses were used to estimate the odds ratio of 30 - and 90 - day adverse outcomes associated with AKD and identify the risk factors of AKD. Results: AKD was developed in 42.3% (419/990) of the study patients, with 186 in AKD stage 1, 107 in AKD stage 2 and 126 in AKD stage 3. Pediatric patients with AKD stage 2 - 3 had significantly higher rates in developing 30 - and 90 - day adverse outcomes than those with AKD stage 0 and 1. The adjusted odds ratio of AKD stage 2 - 3 was 12.18 (95% confidence interval (CI), 7.38 - 20.09) for 30 - day adverse outcomes and decreased to 2.49 (95% CI, 1.26 - 4.91) for 90 - day adverse outcomes. AKI stages 2 and 3, as well as glomerulonephritis were the only predictive factors for AKD stage 2 - 3. Conclusions: AKD is frequent among hospitalized pediatric AKI patients. AKD stage 2 - 3 represents a high - risk subpopulation among pediatric AKI survivors and is independently associated with 30 - and 90 - day adverse outcomes. Awareness of the potential risks associated with AKD stage 2 - 3 and its risk factors may help improve outcomes through careful monitoring and timely intervention.